Putting nature 'to work' through Payments for Ecosystem Services (PES): Tensions between autonomy, voluntary action and the political economy of agri-environmental practice. (February 2019) - Kolinjivadi, Vijay; Mendez, Alejandra Zaga; Dupras, Jérôme
Abstract: In the Canadian province of Prince Edward Island (PEI), producers have been financially incentivized over the past decade to halt soil erosion, improve water quality, and promote habitat for biodiversity through a provincial programme called "Alternative Land Use Services" (ALUS). ALUS is the first example of a provincial-wide application of payments for ecosystem services (PES) in Canada, yet few studies have explored the application of PES in a Canadian context. In this study, we consider the implementation and outcomes of land-use retirement for conservation within the political economy of intensive agriculture, and particularly the processing potato sector of PEI. Producers subscribing to the programme reported that a combination of financial incentive and moral imperatives for land-use protection influenced uptake; however, an underlying concern referred to rising annual costs of production and increasingly tighter margins of return. In this situation, producers have consistently stated that land taken out of production through PES incurs costs on the producer, eventually resulting in intensified production or the search for new land to replace lost yields. While PES itself may be altering behaviour on land-use management, producers have little control over the broader neoliberal market structures to which they belong. As such, we distinguish between "voluntary" participation in PES as embedded within an unsustainable and expansionary industrial agricultural model from the autonomy of farmers to regenerate the social and ecological potential of food production. In regards to regaining autonomy, we offer examples of how farmers collectively organize to negotiate new sets of incentives through mutual aid and risk-sharing within cooperative enterprises. These examples suggest a form of alter-PES that is being established in the shadow of the formal ALUS programme. We argue that PES should valorize individual and collective efforts towards land stewardship in resistance to the social and ecological simplifications of industrial agriculture.